Acesso e permanência na educação profissional tecnológica: um estudo de caso no instituto federal de educação ciência e tecnologia da Paraíba – Ifpb – campus cajazeiras - Souza, Vanda Lúcia Batista dos Santos (2017)
This study aimed to analyze the factors that lead to access and permanence in the Technological Course of Analysis and Development of Systems - ADS, offered by the Federal Institute of Paraíba - IFPB - Campus Cajazeiras. The research is part of the expansion of higher education in Brazil, particularly the resumption of expansion of the Federal Network of Professional and Technological Education. The theoretical bases of this research were a conceptual analysis on access and permanence, a bibliographical review of educational policies, mainly those related to access and permanence, and the development of Vocational and Technological Education in Brazil and Paraíba. The methodological proposal is characterized as a quantitative and qualitative approach based on a case study. Data collection was done through the application of a semi-opened questionnaire sent to the students of the 5th and 6th periods of the ADS Course, through the electronic form Google Drive, and an interview with the Director of Teaching and the Social Worker of the Cajazeiras campus. The results indicated that the factors that lead to access and permanence in the course of ADS are related to the issues of individual and institutional factors, highlighting as predominant aspects the labor market in the area of the course and the motivational conditions (interest, dedication And effort). Regarding the institutional factors, the students pointed that the research, extension and student assistance programs implemented by the institution are determinant for the permanence, but it is necessary to expand them. Finally, as this study is a specific reality it has contributed with reflections on the phenomena of access and permanence in higher education.